INGESTIVE BEHAVIOR OF NATIVE SHEEP KEPT UNDER A CONTROLLED ENVIRONMENT AT DIFFERENT TEMPERATURES - Felipe L. Furtado; José P. Lopes Neto; Dermeval A. Furtado; Raimundo C. M. Rodrigues; Neila L. Ribeiro (Engenharia Agrícola)
ABSTRACT The purpose of this research was to evaluate the ingestive behavior of 24 adult male sheep from the Santa Inês, Morada Nova, Soinga, and without defined racial standard breeds, kept in a controlled environment (climatic chamber), at thermoneutral temperatures (TNT: 20.0; 24.0 and 28 .0 °C) and thermal stress (TSH: 32.0 and 36.0 °C), with its behavior being analyzed at each temperature over a 24-hour period. The design used was randomized with a 4x5 factorial scheme, with four breeds at 5 temperatures. The thermal stress index at temperatures of 20.0, 24.0 and 28.0°C were classified as comfortable, at a temperature of 32.0°C defined as mild to moderate discomfort and at a temperature of 36.0°C classified as alarming. Behavioral changes were similar between breeds, with feeding time being similar among breeds, with an increase in idle time and drinking water and a reduction in rumination time with the elevation of temperature. The animals kept the ability to maintain their ingestive behavior, even in situations of heat stress.